178k views
2 votes
Find the inverse of the given function. f(x)= -1/2SQR x+3, x greater than or equal to -3

User Agis
by
4.7k points

2 Answers

0 votes

Answer:

So, the inverse of function


f(x) = (-1)/(2) √(x+3) is
f^(-1)(x)= 4x^2-3

Explanation:

We need to find the inverse of the given function


f(x) = (-1)/(2) √(x+3)

To find the inverse we replace f(x) with y


y = (-1)/(2) √(x+3)

Now, replacing x with y and y with x


x = (-1)/(2) √(y+3)

Now, we will find the value of y in the above equation

Multiplying both sides by -2


-2x = √(y+3)

Taking square on both sides


(-2x)^2 = (√(y+3))^2


4x^2 = y+3

Finding value of y


y = 4x^2-3

Replacing y with f⁻¹(x)


f⁻¹(x)= 4x^2-3

So, the inverse of function


f(x) = (-1)/(2) √(x+3) is
f^(-1)(x)= 4x^2-3

User MatthewMcGovern
by
5.3k points
1 vote

ANSWER


f^( - 1) (x) =4 {x}^(2)- 3

EXPLANATION

A function will have an inverse if and only if it is a one-to-one function.

The given function is


f(x) = - (1)/(2) √(x + 3) \: \: where \: \: x \geqslant - 3

To find the inverse of this function, we let


y=- (1)/(2) √(x + 3)

Next, we interchange x and y to get,


x=- (1)/(2) √(y+ 3)

We now solve for y.

We must clear the fraction by multiplying through with -2 to get;


- 2x = √(y + 3)

Square both sides of the equation to get:


(- 2x)^(2) = (√(y+ 3)) ^(2)


4x^(2) = y + 3

Add -3 to both sides


4 {x}^(2) - 3 = y

Or


y = 4 {x}^(2)- 3

This implies that,


f^( - 1) (x) =4 {x}^(2)- 3

This is valid if and only if


x \geqslant - 3

User Mikel F
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.